Children's Tourism as a Means of Improving the Motor Activity of Primary School Pupils in Rural Schools - Vladyslav Ruban (Lesya Ukrainka Volyn National University, 2017)
The article contains data on the optimization of the motor activity of pupils of 7-10 years of rural schools by means of tourism. Positive and negative factors that influence the organization of extracurricular work in physical education with children of primary school age in the conditions of rural school are determined. Analysis of their own experimental data made it possible to determine that the volume of motor activity of a high level of rural schoolchildren is unsatisfactory, which does not allow raising the functional reserves of the organism to the proper degree. At the same time, studying the motives and needs of rural schoolchildren for physical activities, it was found that tourism is one of the most popular species. The received results became a basis for working out the program of after-hours physical culture and recreation classes «Young tourists», the content of which is presented in the article.